Exploring the sedative properties of natural molecules from hop cones (Humulus lupulus) as promising natural anxiolytics through GABA receptors and the human serotonin transporter - Belal, Amany; Elballal, Mohammed S.; Al-Karmalawy, Ahmed A.; Hassan, Ahmed H. E.; Roh, Eun Joo; Ghoneim, Mohammed M.; Ali, Mohamed A. M.; Obaidullah, Ahmad J.; Alotaibi, Jawaher M.; Shaaban, Salwa; Elanany, Mohamed A. (Frontiers in Chemistry, 2024)
This research work aimed to identify the main components that are responsible for the sedative properties of hop cones and allocate their targets. This investigation was performed through molecular docking, molecular dynamic simulations, root mean square fluctuation (RMSF) analysis, and DFT calculation techniques. The tested compounds from Humulus lupulus were compared to diazepam and paroxetine. Molecular docking showed that two-thirds of the compounds had a good affinity to gamma-aminobutyric acid (GABA), outperforming diazepam, while only three surpassed paroxetine on the SERT. Compounds 3,5-dihydroxy-4,6,6-tris(3-methylbut-2-en-1-yl)-2-(3-methylbutanoyl)cyclohexa-2,4-dien-1-one (5) and (S,E)-8-(3,7-dimethylocta-2,6-dien-1-yl)-5,7-dihydroxy-2-(4-hydroxyphenyl)chromen-4-one (15) showed stable binding and favorable energy parameters, indicating their potential for targeting GABA receptors and the SERT. This study provides a basis for future clinical research on these promising compounds.